Interest Rate Risk in Banking - Peter DeMarzo; Arvind Krishnamurthy; Stefan Nagel (CESifo GmbH, 2024)
We develop a framework to estimate bank franchise value. Contrary to existing models, sticky deposits and low deposit rate betas do not imply negative duration. While operating costs could generate negative duration, they are offset by fixed interest rate spreads from lending activity. Consequently, franchise value declines as interest rates rise, further exacerbating losses on banks' securities holdings. Banks with less responsive deposit rates tend to invest more in long-term securities, aiming to hedge cash flows rather than market value. Despite significant recent rate hike losses, most U.S. banks still retain sufficient franchise value to remain solvent, justifying forbearance.
Keywords: G21; E43; 330; interest rate risk; bank franchise value; bank solvency; deposit beta